PENGARUH TINGKAT PENDIDIKAN, KEAHLIAN PROFESI, DAN PENGALAMAN KERJA TERHADAP KINERJA PENGAWAS LEMBAGA PERKREDITAN DESA (LPD) DI KECAMATAN GIANYAR - Dewa Ayu Sri Wedanti; Sang Ayu Putu Arie Indraswarawati; I Putu Nuratama (UNHI Press, 2021)
The success of the LPD cannot be separated from the community's commitment to developing and advancing the LPD. The role of the LPD is very important in improving the community's economy. LPD administrators or managers must increase their productivity in order to be able to compete with other financial institutions. Factors that have an influence on the Performance of Village Credit Institutions (LPD) Supervisors are education level, professional expertise, and work experience. This study aims to determine the effect of education level, professional expertise, and work experience on the performance of Village Credit Institution (LPD) supervisors in Gianyar District. The population in this study were all LPDs in Gianyar Subdistrict, with a total of 40 LPDs scattered in each village. The technique of determining the sample in this study using purposive sampling, as many as 30 LPDs that meet the criteria in this study with a total sample of 97 respondents. Furthermore, the data were analyzed using Multiple Linear Regression Analysis Method. The results of this study are the level of education has a positive and significant effect on supervisor performance, professional expertise does not have a significant effect on supervisor performance, work experience has a positive and significant effect on supervisor performance in LPD Gianyar District. There are suggestions that can be given to LPD Gianyar District, namely to improve the performance of supervisors by increasing the education level of employees, increasing professional skills and improving the work experience of employees. As well as adjusting the number of supervisors in the LPD Gianyar District, as it is known that the ideal number of supervisors in each LPD is 3 people.